Perspectives on an Unconventional Partnership Between Occupational Therapists and Pediatric Dental Professionals. - Holsonback, Marissa; Douglas, Reeti; Gazdeck, Leslie (Open Journal of Occupational Therapy (OJOT))
Pediatric clients with disabilities are at increased risk for dental problems, including periodontal disease. Developmental delay and sensory processing dysfunction hinder acceptance of the stimulating dental environment and engagement in oral care routines at home. This health disparity is magnified by many dental professionals' lack of training and confidence with children who have special needs. The holistic occupational therapy scope of practice is inclusive of oral care, pediatric diagnoses, sensory integration, and behavior management, allowing occupational therapists to collaborate with pediatric dental professionals to address the oral health disparity. This perspective manuscript provides occupational therapists with an evidence-supported understanding of the impact oral health has on occupational performance to motivate inclusion of oral care in the therapeutic process, stimulate interdisciplinary collaboration with pediatric dentists, and inspire research on the efficacy of occupational therapy in the dental setting. Proposed collaborative solutions to narrow the present disparity include occupational therapists' referrals to pediatric dental professionals trained in treating youths with disabilities, occupational therapist-led in-service training for dental professionals, concurrent treatment, and joint development of parental educational resources.